The Influence of Work Discipline on the Quality of Excellent Service for Health Administration Staff in Hospital Kediri Regency - Luluk Susiloningtyas; Aris Dwi Cahyono; Bambang Wiseno; Supapak Phetrasuwan (Universitas STRADA Indonesia, 2022)
The quality of excellent service for health administration staff has an important role in maintaining the quality of the hospital. Efforts are needed to improve the quality of excellent service for health administrative staff so that hospital services are more optimal, effective and efficient. One of the efforts to improve the quality of excellent hospital services is to increase work discipline in the provision of health administrative services. The purpose of this study is analyzing the influence of work discipline on the quality of service excellence for health administrative staff in Kediri Hospital. This study was a correlational analytic study that was conducted between August to September 2021 in Kediri Hospital. The research sample is 42 Health Administration staff at Kediri Regency Hospital according to the inclusion criteria and sampling technique used was Acidental Sampling. The dependent variable is the quality of excellent service for health administrative staff.